Transformation of Office Facilities and Infrastructure Role in the Digital Era - Salwa Nur Aulia; Rachma Nadhirah Putri Sanjaya (Asosiasi Ahli Administrasi Indonesia, 2026)
Digital transformation has fundamentally changed the traditional role of office facilities and infrastructure, triggering the evolution from physical offices to smart and hybrid work environments. This study aims to identify the main drivers and synthesize the evolution of the role of facilities and infrastructure in supporting employee work effectiveness in the digital era. The method used is a Systematic Literature Review of 15 reputable primary sources from 2019 to 2025. The synthesis results show that the role of facilities and infrastructure is transforming in three main dimensions: (1) Digital facilities are evolving from paperless offices to AI-based smart automation. (2) Digital infrastructure (such as Cloud Computing) has become the main infrastructure that enables e-working and hybrid work. (3) Physical infrastructure has transformed into a user-centered Smart Workplace, where facility management is integrated with technology (IoT and Digital Twin) for efficiency and comfort. Crucially, the synthesis establishes a new theoretical framework: the interdependency between these three dimensions forms a Strategic Service Infrastructure. It can be concluded that the role of infrastructure has shifted from merely providing a place to supporting flexibility, which requires harmony between physical space and digital infrastructure to achieve optimal work effectiveness, and serves as a predictor for successful hybrid work implementation.